Investigation of the effect of courage behaviors on endurance levels of canoe athletes - Serkan Hacıcaferoğlu; Levent Tanyeri; Orhan T. Emniyet (Physical Education of Students, 2023)
Background and Study Aim. Courage in sports is a concept that has attracted a lot of attention in recent years. It is very important for the athletes to reveal their psychological performance as well as their physical and technical skills during competition and or training times. In this context, this research is important in terms of revealing the mental endurance and courage levels of canoe athletes who struggle not only with their competitors but also with natural conditions.